Beyond Biopolitics : Essays on the Governance of Life and Death - Willse, Craig, 1975-; Clough, Patricia Ticineto, 1945- (Book collections on Project MUSE., 2011)
Under the auspices of neoliberalism, technical systems of compliance and efficiency have come to underwrite the relations among the state, the economy, and a biopolitics of war, terror, and surveillance. In Beyond Biopolitics, prominent theorists seek to account for and critically engage the tendencies that have informed neoliberal governance in the past and are expressed in its reformulation today. As studies of military occupation, the policing of migration, blood trades, financial markets, the war on terror, media ecologies, and consumer branding, the essays explore the governance of life and death in a near-future, a present emptied of future potentialities. The contributors delve into political and theoretical matters central to projects of neoliberal governance, including states of exception that are not exceptional but foundational; risk analysis applied to the adjudication of "ethical" forms of war, terror, and occupation; racism and the management of the life capacities of populations; the production and circulation of death as political and economic currency; and the potential for critical and aesthetic response. Together, the essays offer ways to conceptualize biopolitics as the ground for today's reformulation of governance. --- Book Description.